1983
DOI: 10.1093/bja/55.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrous Oxide on the Epileptogenic Property of Enflurane in Cats

Abstract: A method was developed to standardize the induction of seizure activity during enflurane anaesthesia in cats. The effects of nitrous oxide on the epileptogenic property of enflurane were investigated. A potent anticonvulsant action of nitrous oxide was noted, but partial tolerance to this effect rapidly developed. Some evidence of withdrawal hyperexcitability was also detected. The changes induced by nitrous oxide, despite existing enflurane anaesthesia, suggest that these two anaesthetic agents have different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The synaptic interactions we found may contribute to the in vivo changes. There have been few studies of the synaptic effects of nitrous oxide, despite its wide use, but the transient potentiation of GABA responses which we found are interesting, as transient effects of this anaesthetic have been found on cortical evoked responses (Angel & Gratton, 1982) and on convulsant activity (Stevens, Oshima & Mori, 1983).…”
Section: Temperature Studiesmentioning
confidence: 61%
“…The synaptic interactions we found may contribute to the in vivo changes. There have been few studies of the synaptic effects of nitrous oxide, despite its wide use, but the transient potentiation of GABA responses which we found are interesting, as transient effects of this anaesthetic have been found on cortical evoked responses (Angel & Gratton, 1982) and on convulsant activity (Stevens, Oshima & Mori, 1983).…”
Section: Temperature Studiesmentioning
confidence: 61%
“…During prolonged anaesthesia a state of tolerance develops and sudden cessation of nitrous-oxide induces hyperexcitability. 13 The duration of this case was half an hour so that nitrous-oxide withdrawal-induced hyperexcitability is unlikely.…”
Section: Discussionmentioning
confidence: 90%
“…Data values are expressed as means ± SEM (n = 5 and 6, for N 2 O and control groups, respectively). *P < 0.05 vs control values electroencephalography [9], anticonvulsive actions [10], activation of the dopaminergic system [11], and the enhancement of acetylcholine release [12]. The maximum effects of N 2 O in these studies were observed during the fi rst 30 min, subsiding gradually within 2 h, and then reaching a steady state.…”
Section: Introductionmentioning
confidence: 81%